Eng SYNTHESIS OF POLYOXIDE CATALYSTS AND THEIR APPLICATION POSSIBILITY IN CATALYTIC CONVERSION OF METHANE (Scientific journal of the Fergana State University, 2026)
The aim of this study was to investigate nickel-containing catalysts used for reducing greenhouse gases and the carbonate conversion of methane.  The objects of the study were polyoxide catalysts with the compositions 4NiO∙ZrO2/5Al2O3, 4NiO∙TiO2/5Al2O3 and 3NiO∙TiO2∙ZrO2/5Al2O3, synthesized via sol-gel technology and solution-combustion synthesis based on d-element oxides. The influence of temperature on the process of syngas production through carbonate conversion of methane was examined. The development of cost-effective and highly efficient catalytic systems for the carbonate conversion of methane is crucial for the sustainable production of hydrogen (H₂). To ensure the process is efficient, we studied the application of TiO2∙ZrO2 as a promoter in Ni-containing catalysts, as well as the use of aluminum oxide (Al₂O₃) as a support. Addition of TiO2∙ZrO2 as a promoter resulted in increased basicity and a significant increase in the yield of synthesis gas. Effect of temperature on the carbonate conversion reaction process and concentration of the main conversion products using 4NiO∙ZrO2/5Al2O3, catalyst: at a temperature of 850°C, methane conversion was 87%, and carbon dioxide – 77.1%, when using 4NiO∙TiO2/5Al2O3 catalyst, methane conversion was 71.3%, and carbon dioxide – 65.2%, and when using 3NiO∙TiO2∙ZrO2/5Al2O3 catalyst, methane conversion was 92.1%, and carbon dioxide – 87%.